RECREATIONAL VALUE ESTIMATION OF JAJI-ARYUB PARK USING TRAVEL COST METHOD, PAKTYA, AFGHANISTAN - mujeeb ariez; Abdul Mateen Noori; Khanzadgul Zazai Zazai; Ziaudeen Fahim; Hedayatullah Salari (Jurnal Belantara, 2026)
Protected areas play a vital role in biodiversity conservation and in providing recreational opportunities for the public. Jaji Aryub Park, located in Paktya Province of Afghanistan, is one of such protected area that has become a popular recreational destination over past four years. However, the park’s economic valuation had not been previously documented. For economic valuation of the park this study was conducted using Travel Cost Method (TCM). A total of 250 structured questionnaires were distributed among visitors during the 2024–2025 recreational season, complemented by face-to-face interviews with park administrators. Data were analyzed using SPSS.The findings revealed that the average number of visitors during Eid holidays, Fridays, and regular days was approximately 5,000, 500, and 75 persons per day, respectively. The total number of visitors during the 180-day recreational season of 2024–2025 was estimated 89,800 individuals. About 40% of visitors (35,920 persons) were from neighboring areas (same or adjoining districts), with an average individual expenditure of 300 AFN per person, resulting in a total expenditure of 10,776,000 AFN. The remaining 60% (53,880 visitors) came from distant areas, with an average cost of 2,500 AFN per person, amounting to a total of 134,700,000 AFN. Consequently, the total economic value of the park during the 2024–2025 recreational season was estimated at 145,476,000 AFN (approximately USD 207,822). The study also identified several key challenges affecting the park’s sustainable management and visitors’ satisfaction, including poor infrastructure, restricted areas, noncompliance with environmental protection regulations, and overcrowding during peak recreational periods.